2009
DOI: 10.1007/s11670-009-0081-0
|View full text |Cite
|
Sign up to set email alerts
|

FHL2 interacts with and acts as a functional repressor of Id2 in human neuroblastoma cells

Abstract: Inhibitor of differentiation 2 (Id2) is a natural inhibitor of the basic helix-loop-helix transcription factors. Although Id2 is well known to prevent differentiation and promote cell-cycle progression and tumorigenesis, the molecular events that regulate Id2 activity remain to be investigated. Here, we identified that Four-and-a-half LIM-only protein 2 (FHL2) is a novel functional repressor of Id2. Moreover, we demonstrated that FHL2 can directly interact with all members of the Id family (Id1-4) via an N-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
(68 reference statements)
1
3
0
Order By: Relevance
“…Based on its specific domain structure, FHL2 mediates multiple cellular activities, including gene transcription, signal transduction, apoptosis, and cell proliferation . Some reports have shown that the effect of FHL2 on cells is dependent on regulation of the cytoskeleton, transcription factors, or nuclear receptors . We also found that FHL2 is dependent on cytoskeletal regulation in MCs by colocalizing with F‐actin.…”
Section: Introductionsupporting
confidence: 55%
“…Based on its specific domain structure, FHL2 mediates multiple cellular activities, including gene transcription, signal transduction, apoptosis, and cell proliferation . Some reports have shown that the effect of FHL2 on cells is dependent on regulation of the cytoskeleton, transcription factors, or nuclear receptors . We also found that FHL2 is dependent on cytoskeletal regulation in MCs by colocalizing with F‐actin.…”
Section: Introductionsupporting
confidence: 55%
“…It is likely that other regulatory factors cooperate with Id2 to direct the differentiation of mesodermal progenitors into distinct connective tissues. The functional repressor of Id2, FHL2 gene, might be a good candidate for this function because it is upregulated in micromass cultures treated with NOGGIN (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…FHL2 is involved in many processes, including cell cycle regulation (31,41), apoptosis (55,60), differentiation (21,32,40,63), extracellular matrix assembly (48), bone formation (20), and wound healing (28,65). Although the highest expression of FHL2 occurs in the heart, knockout mice are viable and display no overt cardiac phenotype under basal conditions (5,30).…”
mentioning
confidence: 99%